2018
DOI: 10.1167/iovs.18-24656
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Standard Versus Accelerated Corneal Collagen Cross-Linking for Keratoconus: A Meta-Analysis

Abstract: SCXL has a greater effect in terms of reduction in Kmax than ACXL, while ACXL induces less reduction in CCT and ECD than SCXL. Further well-designed randomized controlled trials comparing ACXL and SCXL are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 84 publications
9
57
0
Order By: Relevance
“…Regarding the corneal thickness changes at the thinnest location, our outcomes are close to other published results 11,19,3133. We recorded a reduction in pachymetry by 17.06 µm at the end of 5 years with an insignificant difference from the last 3 follow-up years values.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding the corneal thickness changes at the thinnest location, our outcomes are close to other published results 11,19,3133. We recorded a reduction in pachymetry by 17.06 µm at the end of 5 years with an insignificant difference from the last 3 follow-up years values.…”
Section: Discussionsupporting
confidence: 90%
“…This may signify that the corneal surface becomes more regular following SCXL. Many authors documented similar findings 11,20. Furthermore, our results showed statistically significant improvement in the corneal asphericity (Q value) which is a good quantified indicator of asphericity of the corneal surface and could be considered as a clue of the optical and visual improvement.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results are similar to those in Kobashi and Tsubota study, which focused on adult population and showed that ACXL has less effect on improving corrected visual acuity than SCXL after 1-year follow-up. 33 Kmax in SCXL was also signi cant lower than those in A-TCXL group (Fig. 7A).…”
Section: Discussionmentioning
confidence: 83%
“…Previously it was reported that for adult patients with keratoconus, transepithelial CXL provided a more protective in uence on corneal thickness than standard CXL. 32 Early meta-analysis showed that accelerated CXL might lead to a less reduction in CCT than standard CXL, 33,34 but recent studies suggests no difference between the ACXL and SCXL when comparing the CCT. 35,36 In pediatric population, our meta-analysis also observed no statistical difference in CCT among different CXL protocols, regardless of different follow-up time (Fig.…”
Section: Discussionmentioning
confidence: 99%